Comparative Clinical Evaluation of Subepithelial Connective Tissue Graft and Acellular Dermal Matrix Allograft for the Treatment of Gingival Recession - F. Haghighati; M. Mousavi; N. Moslemi (Tehran University of Medical Sciences, 2006)
Statement of Problem: Various surgical procedures have been used to achieve root coverage and subepithelial connective tissue graft (SCTG) is identified as one of the most successful techniques. Recently, acellular dermal matrix allograft (ADMA) has been developed as a substitute for SCTG to avoid removing the palatal connective tissue. Purpose: The present study compared the clinical efficiency of ADMA and SCTG in the treatment of recession defects. Materials and Methods: This randomized controlled clinical study, consisted of nine patients with 32 Miller's class I or II recession defects of ≥ 2 mm on the facial aspects of premolar teeth. Bleeding on Probing Index (BPI), Plaque Index (PI), Probing Depth (PD), Recession Depth (RD), Recession Width and Clinical Attachment Level (CAL) were measured at baseline and 6, 12 and 24 weeks post-surgery. Before operation, the samples were randomly allocated to ADMA (test) or SCTG (control) groups. Results: A statistically significant improvement was observed in RD, RW and CAL, but not in BPI, PI and PD. The mean values of changes in all clinical parameters from baseline to 24 weeks postsurgery were not significantly different between the two groups. There was no significant difference in the amount of mean root coverage between the ADMA (85.42%) and SCTG (69.05%) groups (P= 0.058). Conclusion: ADMA may be a useful substitute for SCTG in the treatment of shallow to moderate gingival recessions, if the financial aspect is not an issue for the patient.